Widely Targeted Metabolomics Analysis to Reveal Transformation Mechanism of Cistanche Deserticola Active Compounds During Steaming and Drying Processes - Ai, Ziping; Zhang, Yue; Li, Xingyi; Sun, Wenling; Liu, Yanhong (Frontiers in Nutrition, 2021)
Cistanche deserticola is one of the most precious plants, traditionally as Chinese medicine, and has recently been used in pharmaceutical and healthy food industries. Steaming and drying are two important steps in the processing of Cistanche deserticola. Unfortunately, comprehensive understanding of the chemical composition changes of Cistanche deserticola during thermal processing is limited. In this study, ultraperformance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) based widely targeted metabolomics analysis was used to investigate the transformation mechanism of Cistanche deserticola active compounds during steaming and drying processes. A total of 776 metabolites were identified in Cistanche deserticola during thermal processing, among which, 77 metabolites were differentially regulated (p<0.05) wherein 39 were upregulated (UR) and 38 were downregulated (DR). 47 (17 UR, 30 DR) and 30 (22 UR, 8 DR) differential metabolites were identified during steaming and drying, respectively. The most variation of the chemicals was observed during the process of steaming. Metabolic pathway analysis indicated that phenylpropanoid and flavonoid biosynthesis, as well as alanine metabolism were observed during steaming, while glycine, serine and threonine metabolism, thiamine metabolism and unsaturated fatty acids biosynthesis were observed during drying. The possible mechanisms of the chemical alterations during thermal processing were also provided by KEGG pathway analysis. Furthermore, the blackening of the appearance of Cistanche deserticola mainly occurred in the steaming stage rather than drying stage, which is associated with the amino acids metabolism. All results indicated that the formation of active compounds during the processing of Cistanche deserticola mainly occurred in the steaming stage.